A strategy for selective screening of dual-target bioactive compounds against hypertrophic scar through inhibiting angiotensin II type 1 receptor while stimulating type 2 receptor from Chinese herbs - Lejing Qu; Meizhi Jiao; Zilong Zhang; Yuanyuan Ou; Xue Zhao; Yajun Zhang; Xinfeng Zhao (Chinese Medicine)
Abstract Background Cutaneous hypertrophic scar is a fibro-proliferative hard-curing disease. Recent studies have proved that antagonists of angiotensin II type 1 receptor (AT1R) and agonists of type 2 receptor (AT2R) were able to relieve hypertrophic scar. Therefore, establishing new methods to pursue dual-target lead compounds from Chinese herbs is in much demand for treating scar. Methods To this end, we immobilized AT1R or AT2R onto the surface of silica gel from cell lysates through a specific covalent bond by bioorthogonal chemistry. The columns containing immobilized AT1R or AT2R were jointly utilized to pursue potential bioactive compounds simultaneously binding to AT1R and AT2R from the extract of Rhei Radix et Rhizoma. Their functions on AT1R and AT2R expressions were investigated by in vitro and in vivo experiments. Results Aloe-emodin and emodin were identified as the potential bioactive compounds binding to both of the two receptors, thereby improving the appearance and pathomorphology of hypertrophic scar. They blocked the AT1R pathway to down-regulate the expression of transforming growth factor-β1 (TGF-β1) and stimulate matrix metalloproteinase-1 (MMP-1) expression. As such, the expression of collagen I/III reduced. Conversely, the bindings of the two compounds to AT2R reduced the production of nuclear factor-кB1 (NF-кB1), whereby the generation of interleukin-6 (IL-6) was blocked. Conclusion We reasoned that aloe-emodin and emodin had the potential to become dual-target candidates against hypertrophic scar through the regulation of AT1R and AT2R signaling pathways. It showed considerable potential to become a universal strategy for pursuing multi-target bioactive compounds from Chinese herbs by the utilization of diverse immobilized receptors in a desired order.